Exploratory study on the role of technology in churches. - Chen, Jacqueline Lujun. (2008)
Singapore churches feel the need to adopt technologies to stay relevant in attracting and retaining members. However, technology is not the primary success factor in this area, though it is effective for internal operations and communication. Positioning strategies are also used by some churches to cater to members' needs better.